Herbicide and babassu straw in weed seed bank in cowpea culture (Research, Society and Development, 2021)
The estimation of the seed bank of the infesting population is important in the development of weed control strategies that interfere in the production of crops. The objective of this work was to carry out a survey of the specific composition of the infesting vegetation that constitutes the seed bank in the cowpea culture when associated with the application of babassu straw and herbicides. The experimental design was in randomized blocks in four replications, with the treatments arranged in a simple scheme, distributed in two herbicides (bentazon and fluazifop-p-butyl) and four amounts of babassu straw (0; 5; 10 and 15 t. ha-1). In addition, a weed-infested control was maintained throughout the crop cycle, constituting nine experimental treatments. Babassu palm leaves were collected, crushed and weighed following each treatment and distributed between the lines of the cowpea after the emergence of the crop. The herbicides were applied to seedlings with the second and third fully expanded trifoliate leaf. The seed bank was estimated by taking 50 simple samples, after harvesting the bean crop. The seedlings were quantified and identified, the phytosociological parameters were calculated: relative density (De. R), relative frequency (Fr. R.) and the importance value index (IVI). The floristic composition of the seed bank is represented by the families Poaceae and Cyperaceae. The species Cyperus would and Dactyloctenium aegyptium present the largest number of individuals in the evaluated period. The highest number of viable seeds was obtained in treatment T7 (fluazifop-p-butyl and 10 t ha-1 of straw).